Peran Strategi Pendidikan Pancasila Sebagai Fondasi Karakter dan Masa Depan Bangsa - Jamin, Fikri Ben; Damayanti, Alia; Jelu, Maria Dewi; Hia, Pintau Jul Pilih Niet; Selvia (CV. Kurnia Grup, 2025)
Pancasila education plays a strategic and crucial role in shaping the foundation of national character and preparing Indonesia for a sovereign and dignified future. The challenges of globalization, the rapid flow of information, and the spread of intolerance threaten social cohesion and national identity. This article aims to analyze effective Pancasila education strategies in instilling the noble values of Pancasila as the foundation for character formation in students. Through a qualitative approach and literature review, this research concludes that Pancasila education strategies should not be limited to a cognitive approach (memorization), but must be developed into a values-based, contextual, and participatory education. The application of innovative learning methods, the use of digital technology, and strengthening the role of teachers as role models are key components in transforming Pancasila values into attitudes and behaviors in everyday life. With the right strategy, Pancasila education will not only be a subject but also become the soul of the education system that will produce the next generation of the nation with character, intelligence, and the ability to respond to the challenges of the times, thereby ultimately ensuring the sustainability and glory of Indonesia's future.